Proteomic Technique Identification of Differentially Expressed Proteins of Proteobacteria in Red Sternum Syndrome Mud Crab (Scylla serrata Forsskal, 1775) Hemolymph - Thongsaiklaing, Thanaset (Journal of Mahanakorn Veterinary Medicine, 2020)
Red sternum syndrome mud crab (Scylla serrata Forsskal, 1775) is a poorly understood cause affecting mud crab aquaculture in Thailand. This study presented the differential protein expression in hemolymph between normal mud crab and red sternum syndrome mud crab group I, II and III using 1-dimension sodium dodecyl sulfate polyacrylamide gel electrophoresis. The proteins with size approximately 7.0 and 3.6 kDa were presented in red sternum syndrome mud crab group II and III but were absent in red sternum syndrome mud crab group I and normal mud crab, respectively. The proteins were digested with trypsin and protein lysate were further analyzed by Liquid chromatography–mass spectrometry/mass spectrometry techniques. The results showed 2 protein fragments of 7.0 kDa was consisted of the following amino acid sequences; STFLLDAEGR and YSMLVEDGVIK, respectively. The 3.6 kDa included of only 1 protein fragment, TLEVEVSGPGSQR. The similarity analysis of amino acid sequence with NCBI database, showed all 3 protein fragments were similar to proteins of genus Proteobacteria. Protein is the end product of gene expression. Therefore, bacterial proteins were detected in hemolymph of red sternum syndrome mud crab may likely to be involved in the disease. However, injecting the target bacteria that are expected to cause of disease into normal crab in order to find and identify cause of the disease. Is a way to prevent red sternum syndrome mud crab in the future.